Application-level Communication Services for Development of Social Networking Systems - Yunjin Lee; Mingyu Lim; Yangchan Moon (Institute of Advanced Engineering and Science, 2015)
In this paper, we present our communication middleware (CM), which is designed to reduce the effort of developing common communication functionalities for social networking services (SNSs) in the client-server model. SNS developers can apply the application-level communication services of CM both to an SNS server and to client applications simply by calling application programming interfaces (APIs) and configuring various options related to communication services. CM was developed to enable SNS developers to easily build fundamental services such as transmission of a user-defined event, user membership and authentication management, friend management, content upload and download with different numbers of attachments, chat management, and direct file transfer. All of the communication services also provide options that a developer can customize according to his or her SNS requirements.